20-HETE-mediated cytotoxicity and apoptosis in ischemic kidney epithelial cells - Nilakantan, Vani (2008)
20-HETE, a metabolite of arachidonic acid, has been implicated as a mediator of free radical formation and tissue death following ischemia- reperfusion (IR) injury in the brain and heart. The present study examined the role of this pathway in a simulated IR renal injury model in vitro. Modified self-inactivating lentiviral vectors were generated to stably overexpress murine Cyp4a12 following transduction into LLC-PK(1) cells (LLC-Cyp4a12). We compared the survival of control and transduced LLC-PK(1) cells following 4 h of ATP depletion and 2 h of recovery in serum-free medium. ATP depletion-recovery of LLC-Cyp4a12 cells resulted in a significantly higher LDH release (P < 0.05) compared with LLC-enhanced green fluorescent protein (EGFP) cells. Treatment with the SOD mimetic MnTMPyP (100 µM) resulted in decreased cytotoxicity in LLC-Cyp4a12 cells. The selective 20-HETE inhibitor HET-0016 (10 µM) also inhibited cytotoxicity significantly (P < 0.05) in LLC-Cyp4a12 cells. Dihydroethidium fluorescence showed that superoxide levels were increased to the same degree in LLC-EGFP and LLC-Cyp4a12 cells after ATP depletion-recovery compared with control cells and that this increase was inhibited by MnTMPyP. There was a significant increase (P < 0.05) of caspase-3 cleavage, an effector protease of the apoptotic pathway, in the LLC-Cyp4a12 vs. LLC-EGFP cells (P < 0.05). This was abolished in the presence of HET-0016 (P < 0.05) or MnTMPyP (P < 0.01). These results demonstrate that 20-HETE overexpression can significantly exacerbate the cellular damage that is associated with renal IR injury and that the programmed cell death is mediated by activation of caspase-3 and is partially dependent on enhanced CYP4A generation of free radicals.